PENGARUH DIGITALISASI SISTEM PERPAJAKAN, SOSIALISASI PERPAJAKAN DAN TINGKAT PEMAHAMAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Hendrawan, Agus; Handayani, Nadia (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This research was conducted to determine the effect of digitizing taxation, tax social zation and the level of understanding of taxation on the compliance of  individual tax payers who are registered as employees at PT Angkasa Pura   in 2022, total ng 70 respondents. This research  s a quant tat ve research us ng survey method. Quantitative methods are used to examine certain populations or samples. The sampling technique was carried out randomly. The results of this study  indicate (1) the tax digitization variable has a positive and significant effect on taxpayer compliance, (2) the tax socialization variable is not proven to have a positive effect and does not produce a significant value on tax payer compliance (3) the tax understanding level variable has a positive effect and significantly to taxpayer compliance, and (4) the variables of tax digit zation, tax socialization and the level of understanding of taxation have quite an effect on taxpayer compliance.Keywords: digitalization,  socialization, level of understanding, Tax